A study on the macroeconomic variables that affects the price of Islamic bond (SUKUK) in Malaysian bond market / Siti Diana Atira Zulkifly - Zulkifly, Siti Diana Atira (2015)
The intention to avoid riba has been main contention of the Malaysian people for a very long time. It became a great opportunity for the Malaysian Muslim when a saving scheme was established to help them save enough money for hajj. The tremendous success of this scheme encourages the government to establish the Islamic bank, takaful and Islamic Capital Market. The last decades or so had seen the rapid growth of the Islamic capital market making Malaysia the world‟s leading issuer of Sukuk. However, there are problems encounter with the success of the sukuk issuance in Malaysia such as in terms of cost efficiency, risky and higher cost of capital investment due to lower gain on tax deductibility and shortage of good quality bond issues in the market. Therefore, the objective of this study is to analyze what are the macroeconomic variables that affect the price of Islamic Bond (Sukuk) in Malaysian Bond Market. The macroeconomic variables encountered in the study that affects the price of Islamic Bond are Interest rate, Inflation Rate, Gross Domestic Product and Stock Index. The researcher has conducted a research by using a secondary data for this study. All the data and information were obtained for the year ended 1990 to 2014 from World Bank data and Datastream. In this study, an Eviews 7 was used to analyze a time series of data obtained. There are numerous analysis and tests was conducted by using Eviews 7 in order to analyze what are the macroeconomic variables that affects the price of Islamic Bond (Sukuk) in Malaysian Bond Market. Test that was conducted in order to find the result are Unit Root Test, Normality Test, Descriptive Analysis, Preliminary Analysis, Single Linear Regression and Multiple Linear Regression.